Sistem Pendukung Keputusan Penentuan Lokasi Embung dengan Menggunakan Metode Višekriterijumsko Kompromisno Rangiranje (VIKOR) - Akhmad Ali Sajidin; Ike Pertiwi Windasari; Dania Eridani (Jurnal Terapan Teknologi Informasi, 2023)
Drought is one of the environmental problems that will specifically cause serious problems if it occurs for a prolonged period. One way to overcome this problem is by building reservoirs or small dam as water storage facilities. In Semarang Regency, there are 8 identified locations for small dam candidates, but not all of them can be built within the 5-year budget plan. Decision support systems can be used to determine the priority of candidate small dams based on predetermined criteria, so that budget resources can be utilized optimally. VIKOR (Višekriterijumsko Kompromisno Rangiranje) is one of the Multi-Criteria Decision Making (MCDM) methods used to solve discrete decision-making problems with conflicting criteria. The VIKOR method can be used to rank candidate small dams with multiple criteria. By implementing the VIKOR method into a decision support system, the process of determining the priority of the best small dams in Semarang Regency can be done effectively and efficiently. The information system was developed using the RAD (Rapid Application Development) method with the PHP programming language and MySQL database, and the Codeigniter framework. In the decision support system, the priority ranking for the construction of small dams in Semarang Regency is displayed based on the results of the VIKOR method calculation using several criteria, including topographic factors (vegetation in inundation area, volume of material embankment, and land acquisition area), hydrological factors (live storage/effective storage volume), effectiveness factors (reservoir lifetime and water cost), and accessibility factors (access road to dam's site). The ranking result generated by the decision support system using VIKOR can be used as a reference by decision makers or organizations to improve efficiency in the process of determining the construction of small dams by providing alternative compromise solutions for the best dam options.